Local upregulation of transient receptor potential ankyrin 1 and transient receptor potential vanilloid 1 ion channels in rectosigmoid deep infiltrating endometriosis. Issue 1 (April 2017) - Bohonyi, Noémi; Pohóczky, Krisztina; Szalontai, Bálint; Perkecz, Anikó; Kovács, Krisztina; Kajtár, Béla; Orbán, Lajos; Varga, Tamás; Szegedi, Sarolta; Bódis, József; Helyes, Zsuzsanna; Koppán, Miklós
Transient Receptor Potential Vanilloid 1 (TRPV1) and Transient Receptor Potential Ankyrin 1 (TRPA1) expressed mainly by primary sensory neurons function as major nociceptive integrators. They are also present on the rat endometrium in an oestrogen-regulated manner. TRPV1 is upregulated in peritoneal and ovarian endometriosis patients, but there is no information about TRPA1 and their pathophysiological significances. In this study, patients undergoing laparoscopic surgery were investigated: severe dysmenorrhoea due to rectosigmoid deep infiltrating endometriosis ( n = 15), uterine fibroid-induced moderate dysmenorrhoea ( n = 7) and tubal infertility with no pain ( n = 6). TRPA1 and TRPV1 mRNA and protein expressions were determined by quantitative polymerase chain reaction and semi-quantitative immunohistochemistry from the endometrium samples taken by curettage. Results were correlated with the clinical characteristics including pain intensity. TRPA1 and TRPV1 receptors were expressed in the healthy human endometrium at mRNA and protein levels. Sparse, scattered cytoplasmic TRPA1 and TRPV1 immunopositivities were found in the stroma and epithelial layers. We detected upregulated mRNA levels in deep infiltrating endometriosis lesions, and TRPV1 gene expression was also elevated in autocontrol endometrium of deep infiltrating endometriosis patients. Histological scoring revealed significant TRPA1 and TRPV1 difference between deep infiltrating endometriosis stroma and epithelium, and in deep infiltrating endometriosis epithelium compared to control samples. Besides, we measured elevated stromal TRPV1 immunopositivity in deep infiltrating endometriosis. Stromal TRPA1 and TRPV1 immunoreactivities strongly correlated with dysmenorrhoea severity, as well TRPV1 expression on ectopic epithelial cells and macrophages with dyspareunia. Epithelial TRPA1 and stromal TRPV1 immunopositivity also positively correlated with dyschezia severity. We provide the first evidence for the presence of non-neuronal TRPA1 receptor in the healthy human endometrium and confirm the expression of TRPV1 channels. Their upregulations in rectosigmoid deep infiltrating endometriosis lesions and correlations with pain intensity suggest potential roles in pathophysiological mechanisms of the disease.